AN INTELLIGENT SMART BLACK BOX SYSTEM FOR CRASH RECOVERY - G. Naga Jyothi, B. Maneesha, J. Chinna Babu, N. Nikhil Chandra Reddy, M. Malleswari, M. Manoj (International Journal of Advanced Science and Technology, 2020)
The person who is sitting inside the vehicle faces so many problems due to this accident in an important state of conditions that several vehicles get accident they lost their lives to this heap of person. The project will avoider such type of problems by using different sensor networks. The sensor will work as a providing security to the owner who is inside the vehicle. With these sensor networks some wireless communication technologies are used to alert the person whenever the accident occurs. The person who is the owner of the vehicle he is connecting some mobile communication application to his vehicle with one positioning system for find out the particular location of accident occurrence. The sensor network provides not only provides security to the driver but also used for checking vehicle condition in different situations of the person inside the vehicle. The project is designed to record information such as video recording and live streaming etc. in order to revolutionize the investigation of motor vehicle accidents it can also use to be GPS and GSM technology map vehicles and other vehicles. The raspberry pi 3 module is used to develop this project.